Rancang Bangun Sistem Pengenalan Rambu Petunjuk Arah Berbasis Raspberry Pi Menggunakan Metode OCR (Optical Character Recognition) - Rando Rando; Hurriyatul Fitriyah; Wijaya Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The road sign is one of the means that provides guidance or information to the driver or other road users, about the direction to be taken or the location of the city to go complete with the name and direction of where it is located. Road sign are required so the rider focuses on the road when driving. So that made the system of introduction of raspberry pi-based direction guidance by using OCR (Optical Character Recognition) method, made image processing road sign directions so that riders focus on the road then the information in the form of sound Then the system will separate colors other than green because of the color of the signage signs colored directions green, then the system will look for a box-shaped image, then processing the character of letters and arrows direction, then change the letters that have been detected in the previous process and then recognized to sound. From the test obtained the highest value of 100% and the lowest 0.13% of the characters detected on the signs of direction. The minimum time to execute the image to sound is 4.7 seconds, maximum of 8.02 seconds and 6.402 seconds on average. Based on the results of the research can be concluded that Optical Character Recognition proved able to recognize the detected image on the train data.